Vocative Interjections in Address Forms in Bhojpuri: A Study of Honorifics - Gupta, Ganesh Kumar (Investigationes Linguisticae, 2015)
The present study examines the use of vocative interjections in the address forms and the politeness strategies that could be correlated with the sociocultural variables such as age, gender, kinship, social status, and educational achievements. Toward the end of this study, a situational analysis of the use of the vocative interjections and politeness strategies will also be provided. Since address forms are an important aspect of the interpersonal communication, they manifest both the identity and the status of the speaker and the person addressed (Mehrotra 1986: 80). In this paper, emphasis is put on the speaker’s choice of vocative interjection to mark the different honorific level. It will also purport how sociocultural variables affect the choice of vocative interjection in the address forms.